Structural changes in the side branches and the circle of Willis following the use of flow-diverting stents - Onan, Hasan Bilen; Pehlivan, Umur Anıl; Sözütok, Sinan; Köse, Sevgül; Akgül, Erol (Turkiye Klinikleri, 2022)
Background/aim: This study aimed to evaluate the diameter and flow changes in the circle of Willis and side branches following the use of FDSs extending from the middle cerebral artery (MCA) to the internal carotid artery (ICA) for the treatment of aneurysms in the terminal segment of ICA, and the clinical results. Material and method: This study was conducted in a single center between January 2012 and April 2018 in patients with the anterior choroidal artery (AChoA), the posterior communicating artery (PComA), and the ICA terminal segment aneurysms treated with the FDSs. The changes in aneurysm size, arterial structures covered by the FDSs, and changes in the diameter and flow in arteries forming the circle of Willis were retrospectively analyzed. Results: Fourteen patients with a total of 25 aneurysms treated with FDSs extending from MCA to ICA were evaluated. The mean aneurysm fundus size was 5.14 mm (range 1.5–22 mm). Before treatment, the anterior communicating artery (AComA) was patent in all patients. Implanted FDSs covered the anterior cerebral artery (ACA) and AChoA in all patients (100%), nonhypoplasic PComA in two patients (14.28%), and the ophthalmic artery in nine (64.3%). The mean follow-up time was 36.78 ± 22.44 months. In follow-up, there was a decrease in the mean ipsilateral ACA A1 segment diameter from 1.99 ± 0.58 cm to 1.81 ± 0.31 cm (p = 0.01). The mean contralateral A1 segment diameter increased from 1.66 ± 0.48 cm to 1.93 ± 0.42 cm (p = 0.004). All aneurysms were totally occluded. Conclusion: If the AComA is patent, ipsilateral anterior circulation can be compensated through modifications in the contralateral ACA A1 segment in patients with ICA terminal segment aneurysms treated with FDSs extended from MCA to ICA and covering ACA. Although covering the anterior choroidal and lenticulostriate arteries by FDSs, ischemic complications may not occur frequently. Thus, this effective therapy can be applied more safely.
Keywords: Flow-Diverting Stents; Circle of Willis; Intracranial Aneurysm